INVERSI TOMOGRAFI SEISMIK PANTUL DALAM MENENTUKAN KECEPATAN MEDIA BERLAPIS DENGAN SESAR TUNGGAL - Josep Hutabarat, Paul
Abstract : Estimation of subsurface seismic velocity in multi Iayer media with single fault could be extracted from seismic reflection travel time data, using tomography method with general inverse technique i.e. Marquardt-Lavenberg in combination with SVD (Singular Value Decomposition) and projection technique, SJRT (Simultaneous Iterative Reconstruction Technique). One of the constrains arises from seismic reflection tomography method is sources and receivers laid only on the surface of the earth. The depth and geometry of reflectors are assumed from standard seismic data processing. Langan ray tracing method as a tool for forward modeling calculates the position, orientation, and travel time of the ray path in every model-cell. Result of tomography inversion using combination technique (SVD and Marquradt-Lavenberg) just depends on the acuracy of augmenting damping factor, meanwhile projection technique SIRT reconstructed model with iteratif approximation.